THREE-PORT VERSUS FOUR-PORT LAPAROSCOPIC CHOLECYSTECTOMY - A TWO YEARS EXPERIENCE AT COMBINED MILITARY HOSPITAL MALIR CANTT KARACHI: Three-Port Versus Four-Port Laparoscopic Cholecystectomy - Ali Sheikh, Irfan; Ahmed Memon, Saeed; Misbah Rashid, Muhammad (Pakistan Armed Forces Medical Journal, 2017)
Objective: To compare the safety, outcome and advantages of three port laparoscopic cholecystectomy vs. four port laparoscopic cholecystectomy.Study Design: Prospective descriptive study.Place and Duration of Study: The study was done at Combined Military Hospital Malir Cantt Karachi starting, from Mar 2013 to Oct 2015.Material and Methods: Total 200 patients who had undergone gall bladder removal laparospically were studied. Complication rate, duration of operation, insertion of 4th port, converting laparoscopic method to open, duration of hospital admission, early return to work and need of analgesics were studied in patients with three ports laparoscopic cholecystectomy (LC) vs. four ports LC.Results: A total of 200 patients who had removal gall bladder laparospically, three-port LC were performed in 117 (58.5%) patients and four-port LC was performed in 83 (41.5%) patient. There was no significant difference with respect to complication rate, converting to open technique and duration of operation were comparable to four ports LC. One patient required 4th port in left hypochondrium for liver retractor to retract enlarged left liver lobe.Conclusion: LC using thee ports can be performed safely when done by experts in this method. The said procedure has significant benefits over the conventional four-port method with respect to decreased use of pain killers and duration of hospital admission.